Dripping Test analysis of water loss of frozen chicken carcasses in Rio Branco – AC - França de Oliveira, Mylla; Gelli Feres de Marchi, Patrícia; Toledo Messias, Cassio; Carla Marchi de Rezende-Lago, Naiá; Silveira, Daniela Lacerda Alves da (Seven Editora, 2023)
In 2019, Brazil reached its highest level of production in tons of chicken meat, reaching the mark of 13.245 tons, and registered third place in the world market for chicken meat. In a position of such importance, it is increasingly necessary to standardize and refine the quality of meat and product offered. This project aimed to raise discussion and carry out an analysis of possible frauds regarding the loss of water in chicken carcasses frozen by dripping test, a process that aims to determine whether the meat absorbed excess water during the industrial process, if the carcasses pass the percentage of 6%, allowed by the legislation and by the Ministry of Agriculture, Livestock and Supply (MAPA), they do not follow what is proposed by the legislation. Eighteen samples of frozen chicken carcasses of three different brands were collected. The results obtained through this study indicate that better inspection and control by the Ministry of Agriculture, Livestock and Supply (MAPA) and the agencies responsible for the carcass cooling stage is necessary, given that one of the three brands analyzed was not under what is recommended by the legislation, being subject to notification and fine. DOI: https://doi.org/10.56238/devopinterscie-179